Behaviors assumed by nurses related to the vesical exploration proceedings. - Maria Virgínia Martins Faria Faddul Alves; Claudia Helena Bronzato Luppi; Cybelle Paker (Revista Ciência em Extensão, 2010)
Introduction: Urinary tract infection (UTI) is an inflammation of the urinary passages with associated symptoms and the presence of bacteria in the urine. UTI is responsible for 35 to 45% of all hospital infections (HI) acquired. The great majority of these cases, 80% of UTI, are related to vesicle catheterization, and among hospitalized patients, 10% are exposed to this procedure (RODRIGUES, 1997). Objective: The principal aim of this work is to identify epidemiological aspects of hospital infection occurrence and to verify preparations made by nurses of the inpatient units to control urinary infection.Material and Methods: The researcher collected the data through semistructured interviews, utilizing a questionnaire. 15 nurses, responsible for 15 infirmaries at the university hospital, were interviewed. This work was approved by the Committee of Ethics in Research - OF 272/20004 CEP. Principal results: It was verified that the most frequent topography was respiratory, in 42.1% of the cases, followed by communal and urinary infection, both in 15.8%, skin and soft parts in 10.5% of the responses; and posterior infection of the reproductive system, surgical site and peritoneal infection were each in 5.3% ofresponses. About 73.3% of the nurses knew the indices of hospital infection related to vesicular probing in their infirmary. The hospital has an active CCIH in various infirmaries, including notifying them in relation to infections. With regard to the aspects nurses considered most important to occurrence of urinary infection, 33.3% responded that duration of catheterization had a major influence; 21.2% held that errors in catheter manipulation collaborated to increase indices of infection and 18.2% reported that the gravity of the basic pathology of the patient aggravated the probing situation. The alternative measures utilized to prevent urinary infection were as follows: 29.7% of the nurses use constant evaluation of the catheter; another 29.7% employ a closed drainage system; 21.7% limit catheter use; 16.2% realize training of professionals and 2.7% responded that they orient the patient on intimate hygiene. Conclusions: Given what the nurses demonstrated, they are assuming some attitudes of prevention and adequate treatment as to the risks and benefits of the vesicular probing procedure, thus directing the individualization of nursing precautions. Furthermore, we can emphasize that preventive and alternative measures in catheter use are equivalent, since by utilizing alternative measures the nurse will be able to prevent UTI occurrence.